2015
DOI: 10.3892/ijo.2015.2846
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in patients with esophageal cancer treated with SART1 peptide-pulsed dendritic cell vaccine

Abstract: Abstract.Patients with advanced stage of squamous cell carcinoma of esophagus have a poor prognosis with a lethal outcome. in order to explore the feasibility and effectiveness of dendritic cell (Dc)-based immunotherapy for squamous cell carcinoma of esophagus, we performed a phase Ⅰ/Ⅱ clinical trial of monocyte-derived dendritic cells (moDcs) pulsed with Sart1 peptide in seven patients with advanced stage of this disease. Although the feasibility of this therapy was definite, the effectiveness was not clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…1) involved autologous DCs exposed to autologous tumor-derived RNA, 196 tumor-cell lysates, [197][198][199][200][201][202][203] autologous tumor stem cell lysates, 204 self-renewing and proliferating autologous tumor cells, 205 allogeneic cancer cell line lysates, [206][207][208] TAAs or TAA-derived peptides [209][210][211][212][213][214][215][216][217][218] or a combination thereof. 219 Most clinical studies based on the latter approach preferred melanoma-associated differentiation antigens including premelanosome protein (PMEL; also known as gp100), antigens belonging to the melanoma antigen gene (MAGE) family, tyrosinase (TYR) and Melan-A (MLANA; also known as MART1) (Fig.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) involved autologous DCs exposed to autologous tumor-derived RNA, 196 tumor-cell lysates, [197][198][199][200][201][202][203] autologous tumor stem cell lysates, 204 self-renewing and proliferating autologous tumor cells, 205 allogeneic cancer cell line lysates, [206][207][208] TAAs or TAA-derived peptides [209][210][211][212][213][214][215][216][217][218] or a combination thereof. 219 Most clinical studies based on the latter approach preferred melanoma-associated differentiation antigens including premelanosome protein (PMEL; also known as gp100), antigens belonging to the melanoma antigen gene (MAGE) family, tyrosinase (TYR) and Melan-A (MLANA; also known as MART1) (Fig.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…230 Regarding the distribution across different cancer types ( Fig. 1), patients harboring melanoma were most commonly enrolled in these trials, 186,196,198,205,213,221,223,227,[231][232][233][234] followed by patients with prostate cancer, 206,208,212,215 glioma or glioblastoma (GBM), 185,197,202,219 hepatocellular carcinoma, 204,211,220 non-small cell lung carcinoma (NSCLC), 207,214,230 renal cell carcinoma (RCC), 201,203 esophageal carcinoma, 216,226 and pancreatic ductal adenocarcinoma, 209,217 among others. Of note, only two trials included a wide range of advanced solid tumors refractory to previous treatments.…”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…Thus, it has been suggested that in clinical trials, in order to obtain enhanced vaccine efficiency, peptide-pulsed DCs are immunized mostly via s.c. or i.d. [52][53][54][55][56]. In further studies, a comparison on i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells are one of the most potent antigen-presenting cells capable of ingesting apoptotic tumor cells and presenting tumor-associated antigens to T-cells (83). In pre-clinical studies, DC-based strategies showed strong effects against esophageal carcinoma cell lines (84), and were evaluated in clinical phase I/II studies to assess feasibility and efficacy (85).…”
Section: Esophageal Cancermentioning
confidence: 99%